Blended Learning In Higher Education: A Bibliometric Analysis - Cindy Rosalinda; Neti Budiwati; Irfan Alfaridzi Ramadhan (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This study aims to identify and analyze main information, publication growth, the growth of this journal, growth by institution, research productivity, publications by country, publications by subject, publications by document type, thematic maps, network visualization, overlay visualization, density visualization, relationships between authors. The research used bibliometric method. Collecting data by searching through the Scopus database with the keywords Blended Learning in Higher education with the categories Article title, Abstract, Keywords in the period 2005-2021. Data were analyzed by year, author, origin of author and subject using Microsoft Excel 2010. Meanwhile, the publication development map was analyzed using R-Studio software, and VosViewer. The research results from this article itself found that the USA was the most contributing country regarding the topic of Blended Learning in Higher education with 16 documents and the most productive author on the topic of blended Learning in Higher Education was Najeh Alsalhi from Ajman University with 4 documents. Originality This study is the first to review and map the study of Blended Learning in Higher Education using bibliometric analysis, using data from year to year. All articles published in the journal have been reviewed in terms of methodology, country/country group of cases and topics/subtopics for future research.